An automatic sorting workstation by using robotic arm - Ahmad, Mohd Hussaini (2006)
The main purpose of this project is to fulfil the requirement to complete the degree course in Electrical Engineering. Its objective is to develop problem solving, analysis, synthesis and evaluation skills in the field of Electrical Engineering. The aim of this project was to implement the sorting workstation by using the Programmable Logic Controller (PLC) as the main controller and combined the Robotic Arm as the manipulator. The workstation sorted the valid product in 3 positions. The valid products were only in one range of colour regarding to thereflection light of the surface of products tested.